Selective Ammonia Gas Sensor based on SnO2-APTES Modification. (2016) - Hijazi, M.; Rieu, M.; Stambouli, V.; Tournier, G.; Viricelle, J-P.; Pijolat, C.
Abstract: In the present work, SnO2 sensors were produced by thick film fabrication. In order to deal with well-known lack of selectivity of SnO2 sensors, functionalization was performed. Silanization by 3-aminopropyltriethoxysilane (APTES) in liquid phase was used as an intermediate step, followed by functionalization with molecules bearing acyl chloride with different end functional groups molecules, for example ester group. Modified sensors with APTES and ester end functional group were successfully characterized by attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR). The SnO2 sensor modified with ester end group was found to be sensitive and selective to ammonia gas at 100̊C. Working at low temperature is also one of the advantages of these sensors as well as the selectivity with respect to other gases like acetone.